Second job holding in Germany: A persistent feature? - Philipp Lentge (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
This paper investigates the persistence and determinants of second job holding in Germany, especially marginal second jobs, following a legislative change allowing extensive dispensation of marginal second jobs from taxes and social security contributions. I document an upward trend in second job holding driven in particular by women. Moreover I find strong evidence for the persistence of second job holding using a dynamic panel model. Further, I identify significant gender differences in the decision to moonlight, where especially women in the lower part of the earnings distribution and women with few years of tenure are most likely to take up a second job.
Keywords: J22; J28; 330; second job; marginal second job; multiple job holding